Pembelajaran Pendidikan Anak Usia Dini Online di Era Pandemi Covid-19 - Yusi Srihartini; Maulidia Pratami Lestari (Tarbiatuna: Journal of Islamic Education Studies, 2021)
The online learning system is a solution for the teaching and learning process during the Covid-19 pandemic for all levels of education including early childhood education (PAUD). The research objectives were to obtain an overview of the effectiveness of online learning at the Early Childhood Education (PAUD) level, explain the obstacles and solutions for early childhood teachers in providing online learning, and explain the efforts of teachers in developing early childhood learning in the Covid region. The research subjects were four educators in two Raudhatul Athfal, leuwiliang-bogor sub-districts. Qualitative research design using interview techniques in collecting data. The results showed that the teaching and learning process was carried out online / online even though the learning was not effective due to obstacles including the lack of student motivation and lack of facilities such as cellphones and internet quotas. One solution is offline learning. Pay attention to the aspects of learning as a teacher's effort to achieve learning.